Manifestations of dark personality traits in work contexts: a comparison of sociodemographic variables between Spain and Chile - Bueno de la Fuente, Carla; de la Fuente-Anuncibay, Raquel; Ortega-Sánchez, Delfín; González-Bernal, Jerónimo (Frontiers in Psychology, 2025)
Introduction/objectiveThe Dark Triad of personality (Machiavellianism, narcissism, and subclinical psychopathy) has garnered increasing attention in organizational settings due to its impact on workplace behavior and organizational climate. This study aimed to examine the expression of these traits in work environments in Chile and Spain, taking into account potential differences based on geographic-cultural background, age group, occupation, and gender.MethodA non-experimental cross-sectional design was employed with a sample of 173 employed individuals. The Dark Triad of Personality at Work (TOP) questionnaire was administered, assessing egocentric views of work (EGO), imposing attitudes (IMPO), and impulsive/disengaged styles (NCI).ResultsMale participants scored significantly higher across the three theoretical dimensions and in the subscales of Authority Need and Impulsivity (η2 = 0.026–0.054), although all scores remained within normative ranges. Chilean participants stood out in Leadership Attribution and Risk-Seeking (η2 ≈ 0.03); older adults (64–80 years) exhibited greater feelings of superiority compared to middle-aged adults (42–52 years); and managerial positions were associated with moderate-to-high scores in Leadership Attribution (T ≈ 56; η2 = 0.090). No significant differences were found in the global factors based on country, age, or profession.ConclusionOverall, variables such as gender, geographic background, and organizational hierarchy appear to modulate adaptive expressions of dark personality traits, without reaching dysfunctional levels.